Counter Intuitive Results in a Simple Model of Wage Negotiations - Harold Houba; Gijsbert van Lomwel (Tinbergen Institute, 1998)
Short-term contracts and exogenous productivity growth are introduced in asimple wage bargaining model. The equilibrium utilities corresponding tomilitant union behaviour are independent of the contract length. The wagedynamics are linear if strike is credible (low wage shares) and nonlinearotherwise (high wage shares). The model can admit two steady state wageshares. The one under strike is not credible exceeds the one under strikeis credible. A wage decrease can occur if strike is credible, but neverwhen strike is not credible. In the limit as time between bargaining roundsvanishes only the first paradox survives.
Keywords: C78; J50; 330; wage bargaining; wage dynamics; chaos; strike; Verhandlungstheorie des Lohnes; Produktivität; Arbeitskampf; Theorie